Implementasi Peraturan Daerah Kabupaten Solok Nomor 2 Tahun 2024 Tentang Rencana Perlindungan Dan Pengelolaan Lingkungan Hidup Oleh Walinagari Koto Gadang Guguak Terhadap Pembakaran Terbuka Limbah Padi Oleh Petani - Tri Agustiani; Zalva Zahlia kairaini; Fatima Zahra Noer Hermansyah; Putri Alya Thahira; Arya Langgara Zai; Dafa Anelda Saputra; Elwidarifa Marwenny (CV. ITTC INDONESIA, 2025)
Nagari Koto Gadang Guguak is located in Gunung Talang District, Solok Regency, is one of the areas with high agricultural activity, especially rice and shallots. In this region, straw burning is still widely done as a quick and cheap way to clean the land. However, the environmental impact caused is quite significant, ranging from air pollution to the threat of land fires in the dry season. So far, there has been a regulation that regulates it, namely the Solok Regency Regional Regulation Number 2 of 2024 regarding the Environmental Protection and Management Plan. The existence of this Regional Regulation is important because it can provide legal certainty in the implementation of environmental protection and management in Solok Regency. The limitations of the problems in writing include: 1) Implementation of the Regional Regulation of Solok Regency Number 2 of 2024 concerning the Environmental Protection and Management Plan by the Regent of Koto Gadang Guguak against the practice of open-burning straw by farmers; and 2) Obstacles faced by the Governor of Nagari Koto Gadang Guguak in implementing the Regional Regulation, especially in overcoming the habit of burning straw. To analyze the Limits of the problem, an empirical type of legal research is used using a case approach and a statute approach. So that the conclusion was obtained: 1) The Regional Regulation of Solok Regency Number 2 of 2024 regarding the Environmental Protection and Management Plan by the Regent of Nagari Koto Gadang Guguak against the practice of open straw burning by farmers, and 2) Factors that hinder the implementation of the Regional Regulation of Solok Regency Number 2 of 2024 regarding the Environmental Protection and Management Plan by the Governor of Nagari Koto Gadang Guguak against the practice of open straw burning by farmers.